Ca[LiAlN2]: A Quaternary Nitridoaluminate. Issue 7 (21st December 2012) - Pust, Philipp; Pagano, Sandro; Schnick, Wolfgang
Abstract: Ca[LiAlN2 ] was synthesized from LiAlH4, LiN3, calcium, and lithium metal as fluxing agent in welded‐shut tantalum crucibles at 900 °C. The compound crystallizes in the form of transparent colorless platelets that undergo hydrolysis in air and under moisture. The crystal structure [ P 21 / c (no. 14), a = 5.7587(12) Å, b = 6.8773(14) Å, c = 5.7960(12) Å, β = 90.28(3)°, Z = 4] was solved from single‐crystal X‐ray diffraction data and was confirmed with Rietveld refinement methods and lattice‐energy calculations (Madelung part of lattice energy, MAPLE). Ca[LiAlN2 ] forms layers of edge‐ and vertex‐sharing AlN4 tetrahedra isotypic with LiCaGaN2 . Li + ions are positioned in tetrahedral voids within the [Al2 N2 N4/2 ] layers resulting in a highly condensed structure of Al‐ and Li‐centered polyhedra. Abstract : Ca[LiAlN2 ] was synthesized by high‐temperature synthesis using flux techniques. It represents the first example of a quaternary calcium lithionitridoaluminate with tetrahedral AlN4 and LiN4 units.